SISTEM PAKAR IDENTIFIKASI TERUMBU KARANG (CORAL REEF) MENGGUNAKAN METODE CERTAINTY FACTOR (STUDI KASUS RATAAN TERUMBU KARANG DI PERAIRAN PULAU MENJANGAN BALI)) - I Komang Budi Mas Aryawan (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
Limited number of expert and knowledge and terminology of coral reef that can not be applied generally to all types of coral, a difficulty in the identification of coral reef. This study aims to design and implement an expert system called the identification of coral reefsystem, which system is used to help faculty and students (non-experts) to perform the identification of coral reef that are found on coral reef in the waters of the island of Bali in an optimal deer and efficient in terms of time.This research is engineering a software system, which uses the stages of the procedure the System Development Life Cycle (SDLC). Stages of the SDLC procedure used consists of (1) phase of data collection by using the method of library research, observation and interviews, (2) requirements analysis phase of software that uses the method of certainty factor, (3) stages of design or software design, (4) stages of development of implementation of software, and (5) stages of testing.By using the PHP programming language which is a web-based expert system isexpected to identify coral reef can be used by multiple user without the limitations of space and time.Key words: coral reef, certainty factor